Varda Caivano: The density of the actions - Øvstebø, Solveig 1973- (The Renaissance Society at the University of Chicago, 2015)
Each of London-based artist Varda Caivano's canvases represents an inquiry into the practice of painting, performed over time. Layers of paint are applied, then rubbed, scratched, and reworked to create compositions that recall both the physicality of Abstract Expressionism and the mysticism of Redon. In this tension, Caivano negotiates the legacies of abstract painting with a clarity of means and materials. Self-described as an "old-fashioned painter," Caivano's process is intuitive, playful, and open-ended. She develops several paintings simultaneously in the studio, creating individual works that, when displayed together, contribute distinct phrases to a dynamic whole. In constant flux, the paintings present themselves as vulnerable, unfolding, failing, becoming, and disappearing. While decidedly non-figurative, Caivano's paintings summon the viewer to linger as textures and forms emerge. They particularly evoke a sense of place, sometimes recalling landscapes, though more frequently alluding to inner spaces and otherworldly realms. At the same time, they invite close attention to the canvases' physical properties - their modest size, the range of brush strokes, or the way two colors sit next to each other. For this exhibition, Caivano and curator Øvstebø have assembled a group of the artist's recent works that incorporate drawing more directly into the paintings, representing a new direction in her practice. With a muted palette and sparer markings, their tone is lighter, more suggestive of an elusive narrative than vivid emotion